A Case Report of Sarcoidosis Mimicking Vertebral Metastasis - Anchalia Chandrakumaran; Henry R. Bateman; Rehan Qayyum (Case Reports in Medicine)
A 35-year-old African American male, previously healthy, presented with lower back and bilateral lower extremity pain associated with intermitted night sweats and weight loss. Imaging was concerning diffuse vertebral metastatic lesions. He underwent extensive workup to evaluate for metastatic disease. However, right iliac crest, mediastinal, and left inguinal lymph node biopsies were consistent with sarcoidosis. He was started on methotrexate, folic acid, and prednisone.